Pelatihan Interaktif Literasi Keuangan Digital: Penggunaan QRIS dan Dompet Digital untuk UMKM - Deasy Emalia; Madani Hatta; Sriwidharmanelly Sriwidharmanelly; Fenny Marietza (Annusfy : Journal of Multidisciplinary Research, 2026)
This community service activity aims to encourage the transformation of MSME financial management by improving digital financial literacy. The main focus is to increase understanding of digital payment systems such as QRIS and digital wallets (e-wallets) as safe, efficient, and modern transaction tools. The implementation method used is a combination of lectures or direct material delivery, interactive discussions, and direct practice (hands-on learning) through clinical simulations accompanied by the community service team. The results of the activity indicate that participants' initial understanding of digital technology is still relatively low due to limited access and information, but their interest in adopting the technology is very high. Through this interactive training, 90% of MSME participants found the training materials easy to understand. Furthermore, more than 85% of participants now feel more confident to start implementing QRIS and e-wallets. Therefore, it can be concluded that overall, this community service program has made a significant contribution to strengthening local economic independence, increasing financial inclusion, and encouraging sustainable digital transformation in Tapak Gedung Village, a partner village.